Molecular genetic characteristics of gastric cancers from the surgeon’s point of view - Dubinina, V. G.; Mashukov, A. A.; Lukyanchuk, O. V.; Bilenko, A. A.; Zgura, A. N.; Raciborsky, D. V.; Lee, S. N. (Journal of Education, Health and Sport, 2017)
Dubinina V. G., Mashukov A. A., Lukyanchuk O. V., Bilenko A. A., Zgura A. N., Raciborsky D. V., Lee S. N. Molecular genetic characteristics of gastric cancers from the surgeon’s point of view. Journal of Education, Health and Sport. 2016;6(11):592-621. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.200394 http://ojs.ukw.edu.pl/index.php/johs/article/view/4063 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.11.2016. Revised 22.11.2016. Accepted: 30.11.2016. MOLECULAR GENETIC CHARACTERISTICS OF GASTRIC CANCERS FROM THE SURGEON’S POINT OF VIEW V. G. Dubinina1, A. A. Mashukov2, O. V. Lukyanchuk2, A. A. Bilenko1, A. N. Zgura2, D. V. Raciborsky2, S. N. Lee2 1Odessa National Medical university 2Odessa Regional Oncology center Summary A study on the expression of oncoproteins in stomach` carcinomas, has been turned into a real research basically due to the abundance of results and their comprehensive interpretations. The study carried out on the abdominal onco-surgical department ofOdessaRegionalOncologyCenter, included a study of 188 patients operated on for gastric cancer (GC) between 2007-2011. Inall cases was performed the so-called lymphadenectomy for the principal reason of extensive preventive biopsy of visually unchanged lymph nodes. We spend a multivariate analysis of interactions between the expression of oncoproteins p53, VEGFR-3, erbB2, Ki67 and micro involvement of tumor vasculature (ly, v), the local growth (T), the presence of residual tumor tissue (the R), the degree of tumor differentiation (the G) the degree of regional lymph nodes involvement (N) and type of infiltration (Inf α, β, Inf Υ). Keywords: Stomach cancer, Immunohistochemistry and Oncoproteins.